THE EXTENT OF APPLICATION OF SUSTAINABILITY ACCOUNTING STANDARDS IN IRAQI INSURANCE COMPANIES - Shahd Ali Sahib; Assist. Prof. Dr Yasir Sahib Malik (Scholar Express Journals, 2023)
The aim of the research is to study the FNO103 sustainability accounting standards and their application in Iraqi insurance companies in general. The annual reports of the insurance companies from the period (2016-220) were analyzed by statistical programs. There is a weak percentage in the application of indicators of sustainability accounting standards. According to this conclusion, several recommendations were reached, the most important of which is raising awareness of the issue of sustainability accounting through the publication of research and case studies because the field is relatively new and has not received appropriate attention, especially at the local and Arab levels. Training Iraqi negotiators to increase their skills. In dealing with local and foreign investors, in order to obtain guarantees for the benefit of society that are reflected in the environmental and economic aspects of sustainability., Reporting on substantial sustainability issues with the annual financial reports of companies, as they help to make rational decisions based on the financial and material aspect
Keywords: sustainability accounting; SASB sustainability accounting standards; FNO103 standard